Bisphenol A and Male Fertility: Myths and Realities - Castellini, Chiara; Totaro, Maria; Parisi, Antonio; D'Andrea, Settimio; Lucente, Liana; Cordeschi, Giuliana; Francavilla, Sandro; Francavilla, Felice; Barbonetti, Arcangelo (Frontiers in Endocrinology, 2020)
Bisphenol A (BPA) represents the main chemical monomer of epoxy resins and polycarbonate plastics. The environmental presence of BPA is widespread, and it can easily be absorbed by human body through dietary and transdermal routes, so that more than 90% of the population in western countries displays detectable BPA levels in the urine. As BPA is qualified as an endocrine disruptor, growing concern is rising for possible harmful effects on human health. This review critically discusses the available literature dealing with the possible impact of BPA on male fertility. In rodent models, the in vivo exposure to BPA negatively interfered with the regulation of spermatogenesis throughout the hypothalamic–pituitary–gonadal axis. Furthermore, in in vitro studies, BPA promoted mitochondrial dysfunction and oxidative/apoptotic damages in spermatozoa from different species, including human. To date, the claimed clinical adverse effects on male fertility are largely based on the results from studies assessing the relationship between urinary BPA concentration and conventional semen parameters. These studies, however, produced controversial evidence due to heterogeneity in the extent of BPA exposure, type of population and enrollment setting. Moreover, the cause-effect relationship cannot be established due to the cross-sectional design of the studies as well as the large spontaneous between- and within-subject variability of semen parameters. The best evidence of an adverse effect of BPA on male fertility would be provided by prospective studies on clinically relevant endpoints, including natural or medically assisted pregnancies among men either with different exposure degrees (occupational/environmental) or different clinical conditions (fertile/subfertile).